Case Report: Hepatic Adenoma in a Child With a Congenital Extrahepatic Portosystemic Shunt - Glonnegger, Hannah; Schulze, Maren; Kathemann, Simone; Berg, Sebastian; Füllgraf, Hannah; Tannapfel, Andrea; Gerner, Patrick; Grohmann, Jochen; Niemeyer, Charlotte; Hettmer, Simone (Frontiers in Pediatrics, 2020)
Congenital extrahepatic portosystemic shunts (CEPS), previously also described as Abernethy malformations, are rare malformations in which the extrahepatic portal system directly communicates with the inferior vena cava (IVC) thereby bypassing the liver. A hypoplastic portal vein (PV) exists in most cases. CEPS have been associated with the development of liver nodules, ranging from mostly focal nodular hyperplasia (FNH) to hepatic adenoma (HA) and even hepatocellular carcinoma (HCC). Tumor development in CEPS may be due to changes in perfusion pressures, oxygen supply or endocrine imbalances. It is important to rule out CEPS in children with liver tumors, because resection could impede future shunt occlusion procedures, and benign masses may regress after shunt occlusion. Here, we review the case of a 9-year-old male with CEPS and hepatic nuclear Factor 1-alpha (HNF-1-alpha) inactivated HA to raise awareness of this condition and review histopathological changes in the liver of CEPS.